Tawakal dan Resiliensi Akademik Dalam Setting Blended Learning Pada Mahasiswa Muslim Di Yogyakarta - Fitriani, Annisa; Talitha, Alaqsha Shafa; Riady, Sabrina Aulia; Nashori, Fuad (LPPM Universitas Abdurrab, 2024)
In carrying out their tasks in the learning process, students face various challenges, obstacles and difficulties. The ability to cope with challenges, obstacles and difficulties in the academic world is called academic resilience. One of the assets that can be used to optimize academic resilience is tawakal to Allah. This study aims to find out the relationship between tawakal and academic resilience among muslim students in Yogyakarta. This study uses a correlational quantitative method. There were 101 Muslim students from various universities in Yogyakarta who were the subjects of this research, with 21 male subjects and 80 female subjects, with an average age of 20 years old. The data collection technique used in this research is a non-probability sampling technique, by obtaining samples through a purposive sampling technique. The data collection method uses a questionnaire in the form of a Google form. The measuring instruments used are the Tawakal to Allah Scale from Sartika and Kurniawan and the Academic Resilience Scale from Hardiansyah et al. The results of this research show that students who are surrender to god tend to have high academic resilience.